Effect of obturation technique using a new bioceramic sealer on the presence of voids in flattened root canals - Santos-Junior, Airton Oliveira [UNESP]; Tanomaru-Filho, Mário [UNESP]; Pinto, Jáder Camilo [UNESP]; Tavares, Karina Ines Medina Carita [UNESP]; Torres, Fernanda Ferrari Esteves [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this study was to evaluate the filling ability of a new ready-to-use calcium silicate-based sealer using thermoplastic or single-cone technique in flattened root canals. Twenty-four flattened distal canals of mandibular molars with a buccolingual diameter 4 or more times larger than the mesiodistal diameter were selected. The root canals were prepared and filled (n 12), according to the following techniques: thermoplastic or single-cone technique using Bio-C Sealer. The teeth were scanned using Skycan 1176 micro-computed tomography (micro-CT) voxel size 8.74 μm, before and after filling the root canal. The percentage of voids in the filled root canals was evaluated, and the data were statistically analyzed using the unpaired t-test (α = 0.05). The root canals filled using the thermoplastic technique created a smaller percentage of voids in the cervical/middle thirds than those filled using the single-cone technique (p < 0.05). There was no difference in the percentage of voids using either technique in the apical third (p > 0.05). The flattened root canals in the cervical/middle thirds were better filled using the ready-to-use calcium silicate-based sealer associated to the thermoplastic technique, compared with the single-cone technique. In the apical third, the techniques showed similar filling ability.
Keywords: Endodontics; Root Canal Filling Materials; Root Canal Obturation; X-Ray Microtomography